Evaluating Renal Biomarkers in Diabetic Nephropathy: Significant Variations Across Groups - Botirova Nigina Akram qizi (Zien Journals, 2024)
Diabetic nephropathy (DN) is one of the most serious complications associated with diabetes mellitus (DM) and a leading cause of end-stage renal disease (ESRD) worldwide. DN is characterized by progressive kidney dysfunction, typically manifesting as albuminuria, glomerular hypertrophy, and a gradual decline in the glomerular filtration rate (GFR). Early detection and intervention are crucial to prevent the progression of DN to ESRD, making the study of renal biomarkers an essential aspect of understanding DN's pathophysiology and improving patient outcomes
Keywords: ESRD; improving; pathophysiology; outcomes